Multi attribute decision making: Assessing the technological and operational parameters of an aircraft - Čokorilo, Olja; Gvozdenović, Slobodan; Mirosavljević, Petar; Vasov, Ljubiša (Transport, 2010)
Regional aircraft are playing a significant role in airline operations. This paper considers the problem of selecting an appropriate aircraft from the airline fleet for optimal regional air travel realization. Complexity balance between air travel demand (passengers, goods) and the proposed aircraft capacity presents the priority in airline operations. A principal feature of the methodology considered in this paper is a multi attribute analysis of technological and operational aircraft characteristics (turboprop and turbojet). A comparison of the presented regional aircraft parameters is based on the following criteria: technological (aerodynamic efficiency, structural efficiency, fuel flow at the optional FL, cruise endurance and requested trip fuel for the fixed cruise range), operational (max range with max payload, ground efficiency (aircraft maintainability based on external dimensions) and climb capability. With the aim of defining aircraft rank, the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method was applied. Therefore, the Saaty scale was used for developing the weight of different criteria. The conducted research included a sample of four representative regional aircraft: Do328, CRJ100er, Saab2000 and ERJ145. The results obtained would help in determining the airline fleet or selecting the optional solution from the existing fleet.First published online: 10 Feb 2011